Climate Projections for the Southern Ocean Reveal Impacts in the Marine Microbial Communities Following Increases in Sea Surface Temperature - Tonelli, Marcos; Signori, Camila Negrão; Bendia, Amanda; Neiva, Juliana; Ferrero, Bruno; Pellizari, Vivian; Wainer, Ilana (Frontiers in Marine Science, 2021)
Anthropogenic global warming can have strong impacts on marine ecosystems, especially on climate-sensitive regions such as the Southern Ocean (SO). As key drivers of biogeochemical cycles, pelagic microbial communities are likely to respond to increases in sea surface temperature (SST). Thus, it is critical to understand how SST may change in future scenarios and how these changes will affect the composition and structure of microbial communities. By using a suite of Earth System Models participating in the Coupled Model Intercomparison Project Phase 6 (CMIP6), machine learning, and 16S rRNA sequencing data, we investigated the long-term changes as projected by CMIP6 simulations in SST throughout the twenty first century and the microbial diversity responses in the SO. Four Shared Socioeconomic Pathways (SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5) were considered to assess the SO surface sensitivity to a warming climate. The SST changes across SSPs were ≈0.3, ≈0.7, ≈1.25, and ≈1.6oC between 2015 and 2100, respectively, and the high emissions scenarios projected a much sooner emergence of the human-induced temperature change throughout the SO. The impacts on Antarctic marine diversity of bacteria and archaea are expected to be significant and persistent by the late twenty first century, especially within the higher end of the range of future forcing pathways.